Faktor risiko penularan malaria di desa pamotan Kabupaten pangandaran - Lukman Hakim (ASPIRATOR - Journal of Vector-borne Disease Studies, 2013)
Malaria is a disease that could reemerge depending on the development of risk factors for transmission. So, although now the number of cases of malaria in Pamotan village Pangandaran district has decreased, but will back to increase due to have a history as high malaria endemic areas. To anticipate, the further analysis of research data has been carried out with the aim to identify the transmission risk factors as well as to estimate the emergence of malaria cases. Results of data analysis showed that the risk factors for transmission of malaria in Pamotan village are malaria carrier patient that without clinical symptoms with density 35.08‰, the local malaria transmission (indigenous), outside the region transmission (imports), the high of mobilization of the population, and the presence of Anopheles sundaicus mosquitoes as vectors of malaria with the fluctuating density. It is also known that the population most at risk for malaria transmission is the age group 1-5 years, so it should be a priority in any malaria control activities. The regression test that resulted, if there a source of malaria transmission, rainfall data can be used as a basis for estimating the emergence of malaria cases of in the coming two months. Thus, that the activity planning can be made to anticipate the increasing of malaria transmission in order prevent outbreaks.